(untitled) (Academicia Globe: Inderscience Research, 2022)
This article reveals the current problems and prospects of economic cooperation between Russia and the Middle East countries in the context of new transformations in world politics. The Middle East is considered as a region for strengthening economic rapprochement with Russia in the food, military–technical, and trade spheres.